Natural variation in HsfA2 pre‐mRNA splicing is associated with changes in thermotolerance during tomato domestication. Issue 3 (14th November 2019) - Hu, Yangjie; Mesihovic, Anida; Jiménez‐Gómez, José M.; Röth, Sascha; Gebhardt, Philipp; Bublak, Daniela; Bovy, Arnaud; Scharf, Klaus‐Dieter; Schleiff, Enrico; Fragkostefanakis, Sotirios
Summary: Wild relatives of crops thrive in habitats where environmental conditions can be restrictive for productivity and survival of cultivated species. The genetic basis of this variability, particularly for tolerance to high temperatures, is not well understood. We examined the capacity of wild and cultivated accessions to acclimate to rapid temperature elevations that cause heat stress (HS). We investigated genotypic variation in thermotolerance of seedlings of wild and cultivated accessions. The contribution of polymorphisms associated with thermotolerance variation was examined regarding alterations in function of the identified gene. We show that tomato germplasm underwent a progressive loss of acclimation to strong temperature elevations. Sensitivity is associated with intronic polymorphisms in the HS transcription factor HsfA2 which affect the splicing efficiency of its pre‐mRNA. Intron splicing in wild species results in increased synthesis of isoform HsfA2‐II, implicated in the early stress response, at the expense of HsfA2‐I which is involved in establishing short‐term acclimation and thermotolerance. We propose that the selection for modern HsfA2 haplotypes reduced the ability of cultivated tomatoes to rapidly acclimate to temperature elevations, but enhanced their short‐term acclimation capacity. Hence, we provide evidence that alternative splicing has a central role in the definition of plant fitness plasticity to stressful conditions.